TINJAUAN LOVASTATIN DAN APLIKASINYA - Dudi Hardianto (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2014)
Lovastatin is a drug belonging to statins group that is used to decrease the cholesterol levels in blood. The action mechanism of lovastatin is inhibition of the activity of HMG-CoA reductase enzyme, hence reducing cholesterol production in the liver. Some filamentous fungi produce lovastatin, and Aspergillus terreus is known as the highest lovastatin-producing filamentous fungi, therefore it is generally used for production of lovastatin. Commercial production of lovastatin is based on submerged fermentation. But nowadays solid-state fermentation is becoming an alternative for production of lovastatin. Lovastatin is mainly used for antihypercholeterolemia. Other potential uses of lovastatin include therapy of Alzheimer’s disease, cancer, osteoporosis, Parkinson’s disease, multiple sclerosis, and rheumatoid arthritis.Keywords: Statin, lovastatin, Aspergillus terreus, fermentation, antihypercholeterolemia ABSTRAK Lovastatin merupakan obat golongan statin yang digunakan untuk menurunkan kadar kolesterol dalam darah. Mekanisme kerja lovastatin adalah menghambat enzim HMG-CoA reduktase sehingga produksi kolesterol di dalam hati berkurang. Beberapa kapang berfilamen memproduksi lovastatin dan Aspergillus terreus merupakan kapang penghasil lovastatin tertinggi sehingga digunakan dalam produksi lovastatin. Produksi lovastatin secara komersial menggunakan fermentasi cair tetapi sekarang ini fermentasi padat menjadi alternatif lain untuk memproduksi lovastatin. Lovastatin digunakan terutama untuk antihiperkolesterolemia. Lovastatin juga potensial digunakan untuk pengobatan penyakit alzheimer, kanker, osteoporosis, parkinson, multiple sclerosis, dan rheumatoid arthritis.Kata kunci: Statin, lovastatin, Aspergillus terreus, fermentasi, antihypercholeterolemia